Two dimensional featured one dimensional digital waveguide model for the vocal tract. (September 2015) - Qureshi, Tahir Mushtaq; Syed, Khalid Saifullah
Highlights: A new type of pole-zero transfer function of the vocal tract is obtained. The results are comparable with the standard two dimensional waveguide model. The new model is more efficient than the standard two dimensional waveguide model. The wall and glottal reflection coefficients are used for tuning of the bandwidths. Abstract: A vocal tract model based on a digital waveguide is presented in which the vocal tract has been decomposed into a number of convergent and divergent ducts. The divergent duct is modeled by a 2D-featured 1D digital waveguide and the convergent duct by a one dimensional waveguide. The modeling of the divergent duct is based on splitting the volume velocity into axial and radial components. The combination of separate modeling of the divergent and convergent ducts forms the foundation of the current approach. The advantage of this approach is the ability to get a transfer function in zero-pole form that eliminates the need to perform numerical calculations on a discrete 2D mesh. In this way the present model named as a 2D-featured 1D digital waveguide model has been found to be more efficient than the standard 2D waveguide model and in very good comparison with it in the formant frequency patterns of the vowels /a/, /e/, /i/, /o/ and /u/. The model has two control parameters, the wall and glottal reflection coefficients that can be effectively employed for bandwidth tuning. The model also shows its ability to generate smooth dynamic changes in the vocal tract during the transition of vowels.